Financial flow management of trading companies based on business process modeling - G. N. Byblya; S. N. Tretyakova (Вестник университета)
The issues of process approach implementation in enterprise financial flows management system have been highlighted. The stages of financial flows management within the framework of business processes model have been defined. The advantages of the balanced scorecard have been revealed. The approach to financial flows management based on business process models and their optimization methods has been proposed. The approach to enterprise process management is based on the Deming-Shewhart cycle. The strategic map has been considered as tools for process management and metrics control. The composition of balanced scorecard has been proposed, reflecting the dependence of profit, accounts receivable, and equity turnover rate on the key indicators of cost, fragmentation. and time of fulfilling tasks of the AS-IS and TO-BE business process models. The cause-and-effect relationships between the business processes tasks and a company’s financial performance have been considered. The paper presents the results of the analysis and visualization of the dynamics of change in indicators depending on business process model transformation. In order to reduce risks and increase the efficiency of implementing process optimization results, a number of simulation experiments have been conducted for a company actively developing online sales channels. Practical recommendations have been developed and changes in the key business process management system justified. The system effect from simulation modeling results implementation has been obtained.